2010
DOI: 10.1111/j.1751-1097.2010.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cyclobutane Pyrimidine Dimers Induced by UVB Radiation in Conidia of the Fungi Aspergillus fumigatus, Aspergillus nidulans, Metarhizium acridum and Metarhizium robertsii

Abstract: Conidia are responsible for reproduction, dispersal, environmental persistence and host infection of many fungal species. One of the main environmental factors that can kill and/or damage conidia is solar UV radiation. Cyclobutane pyrimidine dimers (CPD) are the major DNA photoproducts induced by UVB. We examined the conidial germination kinetics and the occurrence of CPD in DNA of conidia exposed to different doses of UVB radiation. Conidia of Aspergillus fumigatus, Aspergillus nidulans and Metarhizium acridu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 71 publications
(179 reference statements)
1
28
0
13
Order By: Relevance
“…Variation in susceptibility of entomopathogenic fungi to UV was also related to the color of conidia, since conidial pigmentation seems to be very efficient in protecting against UV radiation, directly (Braga et al 2006;Rangel et al 2006b;Nascimento et al 2010), or indirectly because enzymes involved in pigment-synthesis pathways are also required for tolerance to abiotic stresses (Fang et al 2010). A study conducted with simulated ultraviolet sunlight reported that conidial color can influence the inactivation of conidia by the radiation, where the UV radiation may be blocked on black conidia whereas penetration of UV may vary for other pigmented conidia (Ignoffo and Garcia 1992).…”
Section: Seeking Fungal Isolates Naturally Tolerant To Uvmentioning
confidence: 98%
See 1 more Smart Citation
“…Variation in susceptibility of entomopathogenic fungi to UV was also related to the color of conidia, since conidial pigmentation seems to be very efficient in protecting against UV radiation, directly (Braga et al 2006;Rangel et al 2006b;Nascimento et al 2010), or indirectly because enzymes involved in pigment-synthesis pathways are also required for tolerance to abiotic stresses (Fang et al 2010). A study conducted with simulated ultraviolet sunlight reported that conidial color can influence the inactivation of conidia by the radiation, where the UV radiation may be blocked on black conidia whereas penetration of UV may vary for other pigmented conidia (Ignoffo and Garcia 1992).…”
Section: Seeking Fungal Isolates Naturally Tolerant To Uvmentioning
confidence: 98%
“…Most UV-tolerant isolates probably can survive a few hours of direct exposure to solar UV radiation, but UV-susceptible isolates succumb. In addition, the exposure of fungi to UV-B (Fernandes et al 2007;Fargues et al 1996;Braga et al 2001d;Nascimento et al 2010) or UV-A (Fargues et al 1997;Braga et al 2001c) may delay conidial germination of survivors and reduce fungal development, which decreases the persistence and efficacy of infective propagules in the field (Zimmermann 1982;Roberts and Campbell 1977). Attempts to overcome these circumstances have focused on selecting strains with natural UV tolerance and on formulating conidia with adjuvants to absorb or to block solar radiation and, thereby, protect fungi from UV radiation.…”
Section: Introductionmentioning
confidence: 97%
“…These are quiescent structures produced by several fungal species for dispersion and environmental persistence. Conidia are dispersed by wind or rain and when deposited on the host plants they germinate and initiate the infectious cycle [1,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Conidia are specialized structures responsible for the dispersion, environmental persistence, and/or host infection of many fungal species (6,(8)(9)(10). After being produced, Colletotrichum conidia remain attached to each other by a mucilage and are dispersed over short distances by rain splash after the mucilage has been dissolved by water, so rates of infection are usually highest during the wettest periods of the growing season (7).…”
mentioning
confidence: 99%